Dental health of 5-year-old children and parents’ perceptions for oral health in the prefectures of Athens and Piraeus in the Attica County of Greece - D. I. KALYVAS, C. M. TAYLOR, V. MICHAS, & N. A. LYGIDAKIS (Paediatric Dentistry, 2006)
This study was undertaken in 2001 in order to investigate the dental health status of 5-year-olds in an urban community within Attica County in Greece and the views of the carers of this age group.